Progress and challenges in the implementation of antimicrobial stewardship programs in 50 hospitals in Mexico - Anahí Dreser; Jennifer Hegewisch-Taylor; María Alejandra Cortés-Ortiz; Gabriel Levy-Hara (Journal of Global Antimicrobial Resistance)
Objectives: Antimicrobial stewardship programs (ASP) aim to improve the quality of medical prescribing and contain antimicrobial resistance (AMR). There is little information on the implementation of ASP in hospitals in Mexico. This study aimed to characterize ASP in a sample of hospitals in Mexico and to identify the facilitators and barriers perceived in their implementation, including the COVID-19 pandemic. Methods: A self-assessment electronic survey was adapted from the CDC and WHO ASP's core elements, considering ASP organization, structure, education, guidelines, interventions, surveillance, monitoring, and reporting processes. The survey was addressed to ASP team leaders in a sample of public and private hospitals carrying out regular antimicrobial stewardship activities in Mexico in 2021 and 2022. Results: Fifty hospitals participated: 32 (64%) public and 18 (36%) private. Fifty-two percent of hospitals had an official ASP document, 12% allocated protected time for ASP professionals, and 34% had an annual plan. Most hospitals had an ASP committee (68%); only 14% allocated funding. Most interventions were restrictive (68%); 61% of hospitals prepared cumulative antibiograms periodically, 54% monitored antimicrobial consumption (DDD/DOT), 44% monitored adherence to guidelines, and 24% monitored the implementation of interventions. The main barriers identified were work overload, insufficient human resources, and hospital reconversion due to COVID-19 (particularly in public hospitals), while the support of hospital authorities was the most important facilitator. Conclusions: This diagnosis provides a baseline for strengthening ASP implementation in the country's hospitals. National and institutional policies should prioritize targeting ASP planning, monitoring, and human resources allocation.